INFLUENCE OF SOCIO-ECONOMICS FACTORS ON AGRICULTURAL COOPERATIVE LOAN ON COCOYAM-BASED FARMERS’ PRODUCTION IN OGUN-STATE, NIGERIA - Onugu, C.U.; Adebayo, O.M.; Shittu K. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the influence of socio-economics factors on agricultural cooperative loan on cocoyam-based farmers’ poduction in Ogun-State, Nigeria. A multistage sampling technique was used to select 100 respondents. Data were collected using structured interview schedules and analyzed using descriptive and inferential statistics. The findings showed the farmers’ average age was 41.5 years. The respondents had an average household size of 4 persons. The results also revealed that farming experience (P<0.0), age (P<0.0) and household size (P<0.0) had positive and statistically significant in influencing cocoyam production among respondents in the study area. The major constraining factors to cocoyam production were insufficient funds 70%, inadequate preservation facilities 68%, inadequate extension contact 65% inadequate storage facilities 62% and low research on cocoyam 57%, with a mean of 3.42, 3.40, 3.37 3.33 and 3.28 respectively. The study therefore recommended that farmers should cut down on some of the cost incurring variables. Government at all levels should help to train and educate cocoyam entrepreneurs in order to exhibit higher levels of entrepreneurial capabilities and efficiency leading to higher farm outputs. Farmers should also encourage themselves to establishment more cooperative societies so that they can have more access to cooperative credit.